Neuronal excitation and permeabilization by 200-ns pulsed electric field: An optical membrane potential study with FluoVolt dye - Pakhomov, Andrei G. (Biochim Biophys Acta, 2017)
Electric field pulses of nano- and picosecond duration are a novel modality for neurostimulation, activation of Ca(2+) signaling, and tissue ablation. However it is not known how such brief pulses activate voltage-gated ion channels. We studied excitation and electroporation of hippocampal neurons by 200-ns pulsed electric field (nsPEF), by means of time-lapse imaging of the optical membrane potential (OMP) with FluoVolt dye. Electroporation abruptly shifted OMP to a more depolarized level, which was reached within <1 ms. The OMP recovery started rapidly (τ = 8–12 ms) but gradually slowed down (to τ > 10 s), so cells remained above the resting OMP level for at least 20–30 s. Activation of voltage-gated sodium channels (VGSC) enhanced the depolarizing effect of electroporation, resulting in an additional tetrodotoxin-sensitive OMP peak in 4–5 ms after nsPEF. Omitting Ca(2+) in the extracellular solution did not reduce the depolarization, suggesting no contribution of voltage-gated calcium channels (VGCC). In 40% of neurons, nsPEF triggered a single action potential (AP), with the median threshold of 3 kV/cm (range: 1.9–4 kV/cm); no APs could be evoked by stimuli below the electroporation threshold (1.5–1.9 kV/cm). VGSC opening could already be detected in 0.5 ms after nsPEF, which is too fast to be mediated by the depolarizing effect of electroporation. The overlap of electroporation and AP thresholds does not necessarily reflect the causal relation, but suggests a low potency of nsPEF, as compared to conventional electrostimulation, for VGSC activation and AP induction.